The Penitentiary System and the Necessities of its Innovation (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The study indicates possible normative and administrative interventions suitable for determining an improvement of life conditions in the context of criminal detention. The analysis moves from the works of the Commission for the innovation of the penitentiary system and is conducted within a more general reflection on the meaning and function of penalty, in the awareness of the unavoidable need to finally ensure a full implementation of the constitutional principles on the matter.
Keywords: Punishment; prison; rights; security; justice